Investigating Use of 5G and AR in School Education - Mimounah Ayed Alhujaili; Nouf Bader Aljabri; Raghad Majid Alharbi; Sahar Abdullah Almutairi; Abdul Ahad Siddiqi (International Journal of Computers and Informatics, 2024)
Augmented Reality (AR) is a transformative technology, that seamlessly blending the virtual and physical worlds to enhance user experiences across various domains. This research paper provides a comprehensive review of the current landscape of AR with its different types, namely, marker-based and marker-less AR, exploring its diverse applications and delving into existing studies that highlight its impact on education. The paper further investigates the symbiotic relationship between AR and Fifth Generation (5G) technology, analyzing how the unprecedented speed, low latency, and increased connectivity offered by 5G networks can amplify the capabilities of AR applications.
Keywords: Augmented Reality; Virtual environments; Education; 5G; Marker